ظاهرة تأخر الزواج في المجتمع البنغلاديشي وسبل علاجها : دراسة تحليلية في ضوء السنة النبوية - محمد، محي الدين خندكار عارف
The purpose of this letter is to study the phenomenon of delayed marriage among young men and women in the Bangladeshi society and to reveal ways of treating it in the light of prophetic traditions. The study began with the concept of late marriage by determining the ages of late marriage before highlighting the factors leading to this phenomenon. Among the most important factors are economic problems and social problems, which boil down to the issues of unemployment, dowry, divorce. he effects of delayed marriage were then brought to the attention of different individuals - both men and women, their families, and the society at large. The researcher followed the extrapolative and descriptive approach in collecting all the issues of delayed marriage, including statements of modern scholars, and experts. The analytical approach was employed by analyzing various talks on the subject and conclude by disclosing the prophetic approaches in dealing with the phenomenon of delayed marriage. The main findings of this study were economic problems and its role at the late age of marriage, and the lack of suitable candidates as one’s husband or wife. Overall, the adverse effects of this phenomenon prevail over the positive effects.